Positive electrode slurry and positive electrode plate of low-temperature power type lithium ion battery and battery

By using nickel-cobalt lithium manganate ternary material (NCM523) with appropriate particle size and specific surface area and an electron transmission network constructed by conductive graphite and carbon nanotubes, the problem of poor charging and discharging performance of lithium-ion batteries in low temperature environments is solved. It realizes the high-rate performance and high power requirements of the battery cell at low temperatures.

CN119480878AActive Publication Date: 2025-02-18CAMEL GRP NEW ENERGY BATTERY XIANGYANG CO LTD

Patent Information

Application Number
CN202411681127.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

现有锂离子电池在低温环境下充放电性能不理想,最大充放电容量和端电压大幅降低,且在极低温下无法充放电,进入‘死电池’状态。

Method used

Nickel-cobalt lithium manganate ternary material (NCM523) is used as the positive electrode active material, with a particle size distribution D50 of 3.0-3.5μm and a specific surface area of ​​1.5-2.0m2/g. An electron transmission network is constructed by adding conductive graphite and carbon nanotubes. , optimize the stirring method to improve material dispersion and contactability.

Benefits of technology

It significantly improves the low-temperature performance of the positive electrode material, improves the rate performance of the battery cell at low temperatures, and meets the high power requirements at low temperatures, especially in 12V or 48V start-stop power applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The low-temperature power type lithium ion battery comprises the positive pole piece, a negative pole piece, an electrolyte and a diaphragm, positive electrode slurry of the positive electrode plate comprises the following components in percentage by weight: 95%-97.5% of a positive electrode active material, 1.5%-3% of a positive electrode conductive agent and 1%-2% of a positive electrode binder; the positive pole piece is prepared by dispersing the components in an N-methyl pyrrolidone solvent and performing wet blade coating; the positive electrode active material is a nickel cobalt lithium manganate ternary material, the particle size distribution D50 of the positive electrode active material is 3.0-3.5 m, and the specific surface area of the positive electrode active material is 1.5-2.0 m < 2 > / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of the conductive graphite is 50-70%; the positive electrode binder is polyvinylidene fluoride; the low-temperature performance of the positive electrode material is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion batteries, and in particular relates to a positive electrode slurry, a positive electrode plate and a battery of a low-temperature power lithium ion battery. Background Art

[0002] In low temperature environment, the charging and discharging performance of lithium-ion batteries is not ideal due to polarization. When commonly used lithium-ion batteries work at -10℃, their maximum charging and discharging capacity and terminal voltage are greatly reduced compared to normal temperature. When the ambient temperature drops to -20℃, the available capacity will even drop to 1 / 3 of the room temperature of 25℃. When the ambient temperature is lower, some lithium batteries can no longer be charged and discharged, and enter a "dead battery" state.

[0003] A Chinese patent (publication number CN106876714A, publication date 2017.6.20) discloses a lithium-ion battery for a car start-stop system, including a lithium iron phosphate positive electrode active material and a particle size (D50<3μm). However, the specific energy of the active material of this positive electrode material is low and the low-temperature discharge platform is low, which cannot meet the high power requirements of the start-stop auxiliary battery cell at low temperatures. The new energy market has huge demand, and the 12 / 48V start-stop and auxiliary system has received widespread attention in the market. This type of power lithium-ion battery has a high demand for the low-temperature performance of the positive electrode material. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide a positive electrode slurry, a positive electrode plate and a battery for a low-temperature power lithium-ion battery, so as to effectively improve the low-temperature performance of the positive electrode material.

[0005] The technical solution of the present invention is: a low-temperature power lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; the following amounts are all mass percentages unless otherwise specified;

[0006] The positive electrode slurry of the positive electrode plate comprises the following components and weight percentages: 95%-97.5% of positive electrode active material, 1.5%-3% of positive electrode conductive agent, and 1%-2% of positive electrode binder; the positive electrode plate is prepared by dispersing the above components in N-methylpyrrolidone (NMP) solvent through wet scraping;

[0007] The positive electrode active material is a nickel-cobalt-manganese-oxide lithium ternary material (NCM523), with a particle size distribution D50 of 3.0-3.5 μm and a specific surface area of ​​1.5-2.0 m 2 / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of conductive graphite accounts for 50%-70%; the positive electrode binder is polyvinylidene fluoride (PVDF);

[0008] 1) The method for preparing the positive electrode sheet comprises the following steps:

[0009] (1) Adding positive electrode active material, conductive graphite, and positive electrode binder into a stirring tank and stirring; dispersing carbon nanotubes in N-methylpyrrolidone solvent to obtain carbon nanotube conductive slurry, wherein the weight percentage of carbon nanotubes is 3-10%, and the weight percentage of N-methylpyrrolidone solvent is 90-97%; then adding 40±4% of the weight percentage of carbon nanotube conductive slurry into the stirring tank and stirring; then adding the remaining carbon nanotube conductive slurry and N-methylpyrrolidone solvent into the stirring tank and continuing to stir; then, gradually adding an appropriate amount of N-methylpyrrolidone solvent into the stirring tank, stirring to obtain a positive electrode slurry, and controlling the solid content ratio to be 60%-65%;

[0010] (2) The positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled to be 65-110 g / m 2 (3) The wet electrode plate is transferred to a baking room and dried at a temperature of 100-120°C to obtain a compacted density of 2.8-3.5 g / cm 3 The positive electrode;

[0011] 2) Preparation of negative electrode sheet: The formula of negative electrode slurry contains the following ingredients in percentage by mass: 90-94% artificial graphite, 1-5% soft carbon, 1-3% conductive agent, 1-2% sodium carboxymethyl cellulose, 1-2% styrene-butadiene rubber, and the balance is deionized water. Artificial graphite, soft carbon, conductive agent, sodium carboxymethyl cellulose, styrene-butadiene rubber and deionized water are added to a stirring tank and wet stirred at a rate of 2000-2500r / min for rotation and 15-25r / min for revolution, and the solid content is controlled to be 50%-55%. Then, it is evenly coated on the negative electrode copper foil collector to obtain a wet electrode plate. The wet electrode plate is transferred to a baking room and the baking temperature is controlled to be 90-95°C for drying. Thereafter, the dried electrode sheet is rolled to obtain a compaction density of 1.2-1.8g / cm 3 The surface density is 40-50g / cm 2 The negative electrode.

[0012] 3) Assembling the positive electrode sheet, the negative electrode sheet and the polypropylene separator coated with alumina ceramic in an aluminum-plastic film, injecting electrolyte, and then performing sealing, forming, and volume separation processes to obtain a finished battery cell; subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0013] The electrolyte consists of a carbonate solvent, a lithium salt and an additive.

[0014] The carbonate solvent consists of 5-15% by mass of ethylene carbonate, 30-35% by mass of dimethyl carbonate and 30-35% by mass of ethyl methyl carbonate; the lithium salt consists of 10-15% by mass of lithium hexafluorophosphate and 5-10% by mass of lithium bis(fluorosulfonyl)imide; the additive consists of 1-2% by mass of lithium difluorooxalatoborate, 1-3% by mass of tributyl borate and 1-2% by mass of vinylene carbonate.

[0015] The diaphragm is one of a polypropylene diaphragm coated with alumina ceramic on one side or a polyethylene diaphragm coated with alumina ceramic on one side.

[0016] The lithium-ion battery includes a start-stop lithium-ion battery and an auxiliary lithium-ion battery.

[0017] The negative electrode slurry is composed of the following components in percentage by mass: 90% of artificial graphite, 5% of soft carbon, 2% of conductive agent, 1% of sodium carboxymethyl cellulose, 2% of styrene-butadiene rubber, and the balance is deionized water.

[0018] A positive electrode slurry for a positive electrode plate of a low-temperature power lithium-ion battery, the positive electrode slurry comprising the following components and weight percentages: 95%-97.5% of positive electrode active material, 1.5%-3% of positive electrode conductive agent, and 1%-2% of positive electrode binder; the positive electrode active material is a nickel cobalt manganese oxide ternary material (NCM523), whose particle size distribution D50 is 3.0-3.5μm and specific surface area is 1.5-2.0m2 / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of conductive graphite is 50%-70%; the positive electrode binder is polyvinylidene fluoride (PVDF).

[0019] A method for preparing the positive electrode slurry as described above comprises the following steps:

[0020] The positive electrode active material, conductive graphite and positive electrode binder are added to a stirring tank, and dry powder is stirred at a revolution speed of 15-30 r / min for 30-60 min; carbon nanotubes are dispersed in N-methylpyrrolidone (NMP) solvent to obtain carbon nanotube conductive slurry, wherein the weight percentage of carbon nanotubes in the carbon nanotube conductive slurry is 3-10%, and the weight percentage of N-methylpyrrolidone (NMP) solvent is 90-97%; the carbon nanotube conductive slurry is divided into two parts, A and B, and then A=40±4% of the carbon nanotube conductive slurry is added to the stirring tank, and the carbon nanotube conductive slurry is stirred at a rotation speed of 200-30 0r / min and revolution 15-25r / min for wetting stirring for 30-60min; then add the remaining carbon nanotube conductive slurry B and N-methylpyrrolidone (NMP) solvent into the stirring tank, and continue stirring for 4-8h at a revolution of 15-25r / min; then, add an appropriate amount of N-methylpyrrolidone (NMP) solvent into the stirring tank gradually, and control the speed of the stirring tank at 4000-5000r / min for rotation and 10-25r / min for revolution, and obtain the positive electrode slurry after stirring for 8-12h, and control the solid content ratio at 60%-65%.

[0021] A method for preparing a positive electrode sheet of a low-temperature power lithium-ion battery, using the positive electrode slurry as described above, comprises the following steps:

[0022] The above positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled to be 65-110g / m 2 ;

[0023] The wet plate is transferred to a baking room and dried at a temperature of 100-120°C to obtain a compacted density of 2.8-3.5 g / cm 3 The positive electrode.

[0024] After research, the inventors found that the appropriate particle size selection has a great influence on the performance of the battery cell. Reducing the particle size of the material particles and shortening the migration path of lithium ions are an effective way to improve the low-temperature performance of the positive electrode material. However, if the particle size is too small, the specific surface area of ​​the material will increase, thereby increasing the side reaction between the material and the electrolyte and reducing the low-temperature performance of the positive electrode material. In addition, by adding two different structures of conductive agents, graphite conductive agent and two-dimensional carbon nanotubes, a cross-linked network for electron transmission is constructed; at the same time, by improving the stirring method, improving the dispersibility of the conductive agent and the positive electrode active material, and promoting the effective contact between the conductive agent and the positive electrode active material, the electron transmission path of the positive electrode material can be enhanced, thereby improving the low-temperature performance of the positive electrode material. Therefore, for the selection and application of positive electrode materials for power-type lithium-ion batteries, it is necessary to regulate the particle size and specific surface area of ​​the positive electrode material, as well as to construct an electronic transmission network that matches this material, and synergistically optimize its ion and electron transmission paths, so as to meet the needs of 12V or 48V start-stop power supply.

[0025] The present invention preferably uses NCM523 as the positive electrode material, the particle size of which is controlled within the range of 3.0-3.5 μm in D50 and 1.5-2.0 m in specific surface area. 2 / g, the particle size is small, the specific surface area is large, and the performance of the battery cell within this range reaches the optimal value. This particle size and specific surface area advantage improves the mass transfer efficiency of the positive electrode material and the electrolyte. On the other hand, the present invention preferably uses an electron transfer network jointly constructed by a graphite conductive agent and two-dimensional carbon nanotubes, wherein the conductive graphite accounts for 50-70%. By adjusting the order of adding the conductive agent and the stirring speed to improve the dispersion properties of the positive electrode particles and the conductive agent, the electron transfer path on the positive electrode material side is improved. The synergistic effect of the above-mentioned mass transfer efficiency and electron transmission capacity improves the rate performance of the battery cell in a low temperature environment, which is beneficial to the use of high-power batteries, especially start-stop and auxiliary power supplies at low temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The electron microscope morphology pictures of the positive electrode materials under the conditions of Comparative Example 1, Comparative Example 2 and Example 1;

[0027] Figure 2 The low-temperature rate performance of cells equipped with different cathode materials at -30°C and different pulse discharge conditions;

[0028] Figure 3 The low-temperature rate performance diagram of battery cells equipped with different positive electrode materials under -20℃, 25C pulse discharge conditions. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the embodiments.

[0030] The positive electrode slurry of the positive electrode plate comprises the following components and weight percentages: 95%-97.5% of positive electrode active material, 1.5%-3% of positive electrode conductive agent, and 1%-2% of positive electrode binder; the positive electrode plate is prepared by dispersing the above components in N-methylpyrrolidone solvent through wet scraping;

[0031] The positive electrode active material is a nickel-cobalt-lithium manganese oxide ternary material, with a particle size distribution D50 of 3.0-3.5 μm and a specific surface area of ​​1.5-2.0 m 2 / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of conductive graphite accounts for 50%-70%; the positive electrode binder is polyvinylidene fluoride;

[0032] 1) The method for preparing the positive electrode sheet comprises the following steps:

[0033] (1) Adding positive electrode active material, conductive graphite, and positive electrode binder into a stirring tank and stirring; dispersing carbon nanotubes in N-methylpyrrolidone solvent to obtain carbon nanotube conductive slurry, wherein the weight percentage of carbon nanotubes is 3-10%, and the weight percentage of N-methylpyrrolidone solvent is 90-97%; then adding 40±4% of the weight percentage of carbon nanotube conductive slurry into the stirring tank and stirring; then adding the remaining carbon nanotube conductive slurry and N-methylpyrrolidone solvent into the stirring tank and continuing to stir; then, gradually adding an appropriate amount of N-methylpyrrolidone solvent into the stirring tank, stirring to obtain a positive electrode slurry, and controlling the solid content ratio to be 60%-65%;

[0034] (2) The positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled to be 65-110 g / m 2 (3) The wet electrode plate is transferred to a baking room and dried at a temperature of 100-120°C to obtain a compacted density of 2.8-3.5 g / cm 3 The positive electrode;

[0035] 2) Preparation of negative electrode sheet: The formula of negative electrode slurry contains the following ingredients in percentage by mass: 90-94% artificial graphite, 1-5% soft carbon, 1-3% conductive agent, 1-2% sodium carboxymethyl cellulose, 1-2% styrene-butadiene rubber, and the balance is deionized water. Artificial graphite, soft carbon, conductive agent, sodium carboxymethyl cellulose, styrene-butadiene rubber and deionized water are added to a stirring tank and stirred to obtain negative electrode slurry, and the solid content ratio is controlled to be 50%-55%. Subsequently, the negative electrode slurry is evenly coated on the negative electrode copper foil collector to obtain a wet electrode plate, and the wet electrode plate is transferred to a baking room, and the baking temperature is controlled to be 90-95°C for drying; thereafter, the dried electrode sheet is roll-pressed to obtain a compaction density of 1.2-1.8g / cm 3 The surface density is 40-50g / cm2 The negative electrode;

[0036] 3) Assembling the positive electrode sheet, the negative electrode sheet and the separator in an aluminum-plastic film, injecting electrolyte, and then performing sealing, forming, and volume separation processes to obtain a finished battery cell; then, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0037] The electrolyte is composed of a carbonate solvent, a lithium salt and an additive. The carbonate solvent is composed of 5-15% by mass of ethylene carbonate, 30-35% by mass of dimethyl carbonate and 30-35% by mass of ethyl methyl carbonate; the lithium salt is composed of 10-15% by mass of lithium hexafluorophosphate and 5-10% by mass of lithium bis(fluorosulfonyl)imide; the additive is composed of 1-2% by mass of lithium difluorooxalatoborate, 1-3% by mass of tributyl borate and 1-2% by mass of vinylene carbonate.

[0038] Example 1

[0039] The mass ratio of NCM523, conductive graphite, carbon nanotubes and PVDF in the positive electrode slurry of the positive electrode sheet is 96:1.2:1:1.8.

[0040] 1. The preparation method of the positive electrode sheet comprises the following steps: (1) NCM523 (D50 = 3.2 μm), conductive graphite, and PVDF are added into a stirring tank in a mass ratio of 96:1.2:1.8, and dry powder is stirred at a speed of 20 r / min for 30 min; carbon nanotubes are dispersed in N-methylpyrrolidone (NMP);

[0041] Prepare a carbon nanotube conductive slurry in a solvent, and adjust the mass percentage of carbon nanotubes in the carbon nanotube conductive slurry to 5%; then add 40% of the mass of the carbon nanotube conductive slurry into a stirring tank, and wet and stir it at a rotation speed of 300r / min and 25r / min for 30min; then add the remaining carbon nanotube conductive slurry and N-methylpyrrolidone (NMP) solvent into the stirring tank, and continue stirring at a rotation speed of 25r / min for 4h; then, add an appropriate amount of NMP solvent into the stirring tank in turn, and control the rotation speed of the stirring tank at 4000r / min and 15r / min, and stir for 12h to obtain a positive electrode slurry, and control the solid content ratio to 63%; (2) evenly coat the positive electrode slurry on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and control the single-sided coating surface density to 75g / m 2 ;

[0042] (3) The wet plate was transferred to a baking room and dried at a temperature of 120°C to obtain a compacted density of 3.0 g / cm 3The positive electrode.

[0043] 2. The preparation method of the negative electrode sheet comprises the following steps: the negative electrode slurry is composed of 90% by mass of artificial graphite, 5% of soft carbon, 2% of conductive agent, 1% of sodium carboxymethyl cellulose, 2% of styrene-butadiene rubber and deionized water, the wet stirring rate is controlled at 2000r / min of rotation and 25r / min of revolution, and the solid content ratio is controlled to be 53%, and then it is evenly coated on the negative electrode copper foil current collector to obtain a wet electrode plate, and the wet electrode plate is transferred to a baking room, and the baking temperature is controlled at 90°C for drying;

[0044] After that, the dried electrode was rolled to obtain a compaction density of 1.2 g / cm 3 The surface density is 40g / cm 2 The negative electrode;

[0045] 3. The lithium ion electrolyte is composed of a solvent, a lithium salt and an additive, wherein the solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 15:30:30; the lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 15:5; the additive is composed of lithium difluorooxalatoborate, tributyl borate and vinylene carbonate in a mass ratio of 2:2:1;

[0046] 4. Assemble the positive electrode sheet, negative electrode sheet and polypropylene separator coated with alumina ceramic described in 1-3 in an aluminum-plastic film, inject the electrolyte composed of the above solvent, lithium salt and additives, and then perform sealing, formation and volume separation processes to obtain a finished battery cell. Subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0047] Example 2

[0048] The mass ratio of NCM523 (D50=3.5 μm), conductive graphite, carbon nanotubes, and PVDF in the positive electrode slurry of the positive electrode sheet is 97.5:0.75:0.75:1.

[0049] 1. The preparation method of the positive electrode sheet comprises the following steps: (1) NCM523 (D50 = 3.5 μm), conductive graphite and PVDF are added into a stirring tank in a mass ratio of 97.5:0.75:1, and dry powder is stirred for 40 min at a revolution speed of 25 r / min; carbon nanotubes are dispersed in N-methylpyrrolidone (NMP) solvent to prepare a carbon nanotube conductive slurry, and the mass percentage of carbon nanotubes in the carbon nanotube conductive slurry is adjusted to 6%; then 40% of the mass of the conductive slurry is added into a stirring tank, and the stirring tank is stirred at a rotation speed of 300 r / min and a revolution speed of 20 r / min. min for wetting stirring for 30 min; then, the remaining carbon nanotube conductive slurry and N-methylpyrrolidone (NMP) solvent are added to the stirring tank, and stirring is continued for 4 h at a revolution speed of 25 r / min; then, an appropriate amount of NMP solvent is added to the stirring tank in succession, and the stirring tank speed is controlled at 5000 r / min of rotation and 25 r / min of revolution, and the positive electrode slurry is obtained after stirring for 8 h, and the solid content is controlled at 65%; (2) the positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled at 80 g / m 2 (3) The wet electrode plate was transferred to a baking room and dried at a temperature of 100°C to obtain a compacted density of 2.8 g / cm 3 The positive electrode.

[0050] 2. The preparation method of the negative electrode sheet comprises the following steps: the negative electrode slurry is composed of 92% by mass of artificial graphite, 3% of soft carbon, 3% of conductive agent, 1% of sodium carboxymethyl cellulose, 1% of styrene-butadiene rubber and deionized water, the wet stirring rate is controlled at 2000r / min of rotation and 25r / min of revolution, and the solid content ratio is controlled to be 55%, and then it is evenly coated on the negative electrode copper foil collector to obtain a wet electrode plate, and the wet electrode plate is transferred to a baking room, and the baking temperature is controlled at 90°C for drying;

[0051] After that, the dried electrode was rolled to obtain a compaction density of 1.5 g / cm 3 The surface density is 45g / cm 2 The negative electrode;

[0052] 3. The lithium ion electrolyte is composed of a solvent, a lithium salt and an additive, wherein the solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 5:35:35; the lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 15:5; the additive is composed of lithium difluorooxalatoborate, tributyl borate and vinylene carbonate in a mass ratio of 2:1.5:1.5;

[0053] 4. Assemble the positive electrode sheet, negative electrode sheet and polyethylene separator coated with alumina ceramic described in 1-3 in an aluminum-plastic film, inject the electrolyte composed of the above solvent, lithium salt and additives, and then perform sealing, formation and volume separation processes to obtain a finished battery cell. Subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0054] Example 3

[0055] The mass ratio of NCM523 (D50=3.0 μm), conductive graphite, carbon nanotubes and PVDF in the positive electrode slurry of the positive electrode sheet is 97:1:1:1.

[0056] 1. The preparation method of the positive electrode sheet comprises the following steps: (1) NCM523 (D50 = 3.0 μm), conductive graphite, and PVDF are added to a stirring tank in a mass ratio of 97:1:1, and dry powder stirring is performed for 30 minutes at a revolution speed of 30 r / min; carbon nanotubes are dispersed in N-methylpyrrolidone (NMP) solvent to prepare a carbon nanotube conductive slurry, and the mass percentage of carbon nanotubes in the carbon nanotube conductive slurry is adjusted to 8%; then 40% of the mass of the conductive slurry is added to a stirring tank, and the stirring tank is stirred at a rotation speed of 300 r / min and a revolution speed of 25 r / min. The stirring tank is wetted and stirred at a speed of 30 minutes; thereafter, the remaining carbon nanotube conductive slurry and N-methylpyrrolidone (NMP) solvent are added to the stirring tank, and the stirring is continued at a revolution speed of 25 r / min for 8 hours; subsequently, an appropriate amount of NMP solvent is added to the stirring tank in succession, and the stirring tank speed is controlled at 4000 r / min of rotation and 15 r / min of revolution. After stirring for 12 hours, a positive electrode slurry is obtained, and the solid content is controlled at 60%; (2) the positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled at 75 g / m 2 (3) The wet electrode plate was transferred to a baking room and dried at a temperature of 110°C to obtain a compacted density of 3.5 g / cm 3 The positive electrode.

[0057] 2. The preparation method of the negative electrode sheet comprises the following steps: the negative electrode slurry is composed of 94% by mass of artificial graphite, 1% of soft carbon, 2% of conductive agent, 1% of sodium carboxymethyl cellulose, 2% of styrene-butadiene rubber and deionized water, and the wet stirring rate is controlled at 2000r / min of rotation and 25r / min of revolution.

[0058] The solid content ratio was controlled to be 55%, and then it was evenly coated on the negative electrode copper foil current collector to obtain a wet electrode plate. The wet electrode plate was transferred to a baking room and the baking temperature was controlled to be 95°C for drying. After that, the dried electrode plate was rolled to obtain a compaction density of 1.8g / cm 3 The surface density is 48g / cm2 The negative electrode;

[0059] 3. The lithium ion electrolyte is composed of a solvent, a lithium salt and an additive, wherein the solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 15:30:30; the lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 10:10; the additive is composed of lithium difluorooxalatoborate, tributyl borate and vinylene carbonate in a mass ratio of 2:2:1;

[0060] 4. Assemble the positive electrode sheet, negative electrode sheet and polypropylene separator coated with alumina ceramic described in 1-3 in an aluminum-plastic film, inject the electrolyte composed of the above solvent, lithium salt and additives, and then perform sealing, formation and volume separation processes to obtain a finished battery cell. Subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0061] Comparative Example 1

[0062] This comparative example provides a low-temperature power lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator;

[0063] 1. The preparation method of the positive electrode sheet comprises the following steps: (1) NCM523 (D50 = 2.2 μm), conductive graphite, and PVDF are added to a stirring tank in a mass ratio of 96:1.2:1.8, and dry powder stirring is performed for 30 minutes at a revolution speed of 30 r / min; 1% by mass of carbon nanotubes are dispersed in N-methylpyrrolidone (NMP) solvent to prepare a carbon nanotube conductive slurry, and the mass percentage of the carbon nanotubes is adjusted to 6%; then 40% by mass of the conductive slurry is added to the stirring tank, and the stirring tank is stirred at a rotation speed of 300 r / min and 25 r / min. The mixture was stirred at a speed of 30 minutes; then, the remaining carbon nanotube conductive slurry and N-methylpyrrolidone (NMP) solvent were added to the stirring tank, and the stirring was continued at a revolution speed of 25 r / min for 4 hours; then, an appropriate amount of NMP solvent was added to the stirring tank in succession, and the speed of the stirring tank was controlled at 4000 r / min and 15 r / min, and the positive electrode slurry was obtained after stirring for 12 hours, and the solid content was controlled at 63%; (2) the positive electrode slurry was evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density was controlled at 75 g / m 2 (3) Transfer the wet plate to the baking room and control the baking temperature at 120°C.

[0064] After drying, the compacted density is 3.0 g / cm 3 The positive electrode;

[0065] 2. The preparation method of the negative electrode sheet comprises the following steps: the negative electrode slurry is composed of 90% by mass

[0066] The wet stirring rate is controlled at 2000r / min of rotation and 25r / min of revolution, and the solid content ratio is controlled to be 53%. Then, the wet plate is evenly coated on the negative electrode copper foil current collector to obtain a wet plate. The wet plate is transferred to a baking room and the baking temperature is controlled at 90°C for drying. Thereafter, the dried electrode is rolled to obtain a compacted density of 1.2g / cm 3 The surface density is 40g / cm 2 The negative electrode;

[0067] 3. The lithium ion electrolyte is composed of a solvent, a lithium salt and an additive, wherein the solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 15:30:30; the lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 15:5; the additive is composed of lithium difluorooxalatoborate, tributyl borate and vinylene carbonate in a mass ratio of 2:2:1;

[0068] 4. Assemble the positive electrode sheet, negative electrode sheet and polypropylene separator coated with alumina ceramic described in 1-3 in an aluminum-plastic film, inject the electrolyte composed of the above solvent, lithium salt and additives, and then perform sealing, formation and volume separation processes to obtain a finished battery cell. Subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0069] Comparative Example 2

[0070] This embodiment provides a low-temperature power lithium-ion battery, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator;

[0071] 1. The preparation method of the positive electrode sheet comprises the following steps: (1) NCM523 (D50 = 5.4 μm), conductive graphite, and PVDF are added into a stirring tank in a mass ratio of 96:1.2:1.8, and dry powder is stirred at a speed of 25 r / min for 30 min; 1% by mass of carbon nanotubes are dispersed in N-methylpyrrolidone (NMP) solvent to prepare a carbon nanotube conductive slurry, and the mass percentage of the carbon nanotubes is adjusted to 6%; then the conductive slurry is added into The stirring tank is wetted and stirred at a speed of 300 r / min and 25 r / min for 4.5 hours; then, an appropriate amount of NMP solvent is added to the stirring tank gradually, and the stirring tank speed is controlled at 4000 r / min and 15 r / min, and the positive electrode slurry is obtained after stirring for 12 hours, and the solid content is controlled at 63%; (2) The positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-sided coating surface density is controlled at 75 g / m 2(3) The wet plate was transferred to a baking room and dried at a temperature of 120°C to obtain a compacted density of 3.0 g / cm 3 The positive electrode.

[0072] 2. The preparation method of the negative electrode sheet comprises the following steps: the negative electrode slurry is composed of 90% by mass of artificial graphite, 5% of soft carbon, 2% of conductive agent, 1% of sodium carboxymethyl cellulose, 2% of styrene-butadiene rubber and deionized water, and the wet stirring rate is controlled at 2000r / min of rotation and 25r / min of revolution.

[0073] The solid content ratio was controlled to be 53%, and then it was evenly coated on the negative electrode copper foil current collector to obtain a wet electrode plate. The wet electrode plate was transferred to a baking room and the baking temperature was controlled to be 90°C for drying. After that, the dried electrode plate was rolled to obtain a compaction density of 1.2g / cm 3 The surface density is 40g / cm 2 The negative electrode;

[0074] 3. The lithium ion electrolyte is composed of a solvent, a lithium salt and an additive, wherein the solvent is composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a mass ratio of 15:30:30; the lithium salt is composed of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in a mass ratio of 15:5; the additive is composed of lithium difluorooxalatoborate, tributyl borate and vinylene carbonate in a mass ratio of 2:2:1;

[0075] 4. Assemble the positive electrode sheet, negative electrode sheet and polypropylene separator coated with alumina ceramic described in 1-3 in an aluminum-plastic film, inject the electrolyte composed of the above solvent, lithium salt and additives, and then perform sealing, formation and volume separation processes to obtain a finished battery cell. Subsequently, the finished battery cell is subjected to rate performance tests under different temperatures and different pulse current conditions.

[0076] Figure 1 The electron microscope morphology pictures of the positive electrode materials under the conditions of Comparative Example 1, Comparative Example 2 and Example 1. (a) The positive electrode material of Comparative Example 1, D50 is 2.2 μm; (b) The positive electrode material of Example 1, D50 is 3.2 μm; (c) The positive electrode material of Comparative Example 2, D50 is 5.4 μm.

[0077] Figure 2 The figure shows the low temperature rate performance of the battery cells equipped with different positive electrode materials at -30°C and different pulse discharge conditions. Under the conditions of -30°C and 270A maximum pulse discharge, the discharge lower limit voltage value of the battery cell of Example 1 is 2.62V, which is higher than the lower limit voltage value of 2.48V of Comparative Example 1 and the lower limit voltage of 2.40V of Comparative Example 2.

[0078] Figure 3The figure shows the low temperature rate performance of cells equipped with different positive electrode materials under -20℃, 25C pulse discharge conditions. Under -20℃, 425A continuous pulse discharge conditions, the discharge lower limit voltage value of the cell of Example 1 is 2.59V, and the lower limit voltage value of the cells of Comparative Examples 1 and 2 drops to 2.0V within 2s, which cannot meet the start-stop requirements of the car.

Claims

1. A low-temperature power lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The positive electrode slurry of the positive electrode plate comprises the following components and weight percentages: 95%-97.5% of positive electrode active material, 1.5%-3% of positive electrode conductive agent, and 1%-2% of positive electrode binder; the positive electrode plate is prepared by dispersing the above components in N-methylpyrrolidone solvent through wet doctor blade coating; The positive electrode active material is a nickel-cobalt-lithium manganese oxide ternary material, with a particle size distribution D50 of 3.0-3.5 μm and a specific surface area of ​​1.5-2.0 m 2 / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of conductive graphite accounts for 50%-70%; the positive electrode binder is polyvinylidene fluoride; 1) The method for preparing the positive electrode sheet comprises the following steps: (1) Add positive electrode active material, conductive graphite and positive electrode binder into a stirring tank and stir; disperse carbon nanotubes in N-methylpyrrolidone solvent to obtain carbon nanotube conductive slurry, wherein the weight percentage of carbon nanotubes is 3-10% and the weight percentage of N-methylpyrrolidone solvent is 90-97%; then add 40±4% of the weight percentage of carbon nanotube conductive slurry into the stirring tank and stir; then add the remaining carbon nanotube conductive slurry and N-methylpyrrolidone solvent into the stirring tank and continue stirring; then, add appropriate amount of N-methylpyrrolidone solvent into the stirring tank in turn, stir to obtain positive electrode slurry, and control the solid content ratio to be 60%-65%; (2) evenly coat the positive electrode slurry on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and control the single-sided coating surface density to be 65-110 g / m 2 (3) Transfer the wet plate to a baking room and dry it at a temperature of 100-120°C to obtain a compacted density of 2.8-3.5 g / cm 3 The positive electrode; 2) Preparation of negative electrode sheets: The formula of the negative electrode slurry contains the following ingredients in percentage by mass: 90-94% artificial graphite, 1-5% soft carbon, 1-3% conductive agent, 1-2% sodium carboxymethyl cellulose, 1-2% styrene-butadiene rubber, and the balance is deionized water. Artificial graphite, soft carbon, conductive agent, sodium carboxymethyl cellulose, styrene-butadiene rubber and deionized water are added to a stirring tank and stirred to obtain negative electrode slurry, and the solid content ratio is controlled to be 50%-55%. Subsequently, the negative electrode slurry is evenly coated on the negative electrode copper foil collector to obtain a wet electrode plate. The wet electrode plate is transferred to a baking room and the baking temperature is controlled to be 90-95°C for drying; thereafter, the dried electrode sheet is roll-pressed to obtain a compaction density of 1.2-1.8 g / cm 3 The surface density is 40-50g / cm 2 The negative electrode; 3) Assembling the positive electrode sheet, negative electrode sheet and separator in the aluminum-plastic film, injecting electrolyte, and then performing sealing, forming and volume separation processes to obtain a finished battery cell; Subsequently, the finished battery cell was subjected to rate performance tests under different temperatures and pulse current conditions.

2. The low-temperature power lithium-ion battery according to claim 1, characterized in that: The electrolyte consists of a carbonate solvent, a lithium salt and an additive.

3. The low temperature power lithium ion battery according to claim 2, characterized in that: The carbonate solvent consists of 5-15% by mass of ethylene carbonate, 30-35% by mass of dimethyl carbonate and 30-35% by mass of ethyl methyl carbonate; the lithium salt consists of 10-15% by mass of lithium hexafluorophosphate and 5-10% by mass of lithium bis(fluorosulfonyl)imide; the additive consists of 1-2% by mass of lithium difluorooxalatoborate, 1-3% by mass of tributyl borate and 1-2% by mass of vinylene carbonate.

4. The low temperature power lithium ion battery according to claim 1, characterized in that: The diaphragm is one of a polypropylene diaphragm coated with alumina ceramic on one side or a polyethylene diaphragm coated with alumina ceramic on one side.

5. The low temperature power lithium ion battery according to claim 1, characterized in that: The lithium-ion battery includes a start-stop lithium-ion battery and an auxiliary lithium-ion battery.

6. The low-temperature power lithium-ion battery according to claim 1, characterized in that: The negative electrode slurry is composed of the following components in percentage by mass: 90% artificial graphite, 5% soft carbon, 2% conductive agent, 1% sodium carboxymethyl cellulose, 2% styrene-butadiene rubber, and the balance is deionized water.

7. The low-temperature power lithium-ion battery according to claim 1, characterized in that: In the preparation of the negative electrode sheet, artificial graphite, soft carbon, conductive agent, sodium carboxymethyl cellulose, styrene-butadiene rubber and deionized water are stirred by wet stirring, and the wet stirring rate is controlled at 2000-2500 r / min for rotation and 15-25 r / min for revolution.

8. A positive electrode slurry for a positive electrode plate of a low-temperature power lithium-ion battery, characterized in that: The positive electrode slurry of the positive electrode plate includes the following components and weight percentages: 95%-97.5% positive electrode active material, 1.5%-3% positive electrode conductive agent, and 1%-2% positive electrode binder; the positive electrode active material is a ternary material of nickel cobalt lithium manganese oxide, with a particle size distribution D50 of 3.0-3.5µm and a specific surface area of ​​1.5-2.0m 2 / g; the positive electrode conductive agent is composed of conductive graphite and carbon nanotubes, and the weight percentage of conductive graphite accounts for 50%-70%; the positive electrode binder is polyvinylidene fluoride.

9. A method for preparing a positive electrode slurry as claimed in claim 8, characterized in that: The following steps are involved: The positive electrode active material, conductive graphite and positive electrode binder are added to a stirring tank, and dry powder is stirred for 30-60 minutes at a speed of 15-30 r / min; the carbon nanotubes are dispersed in N-methylpyrrolidone solvent to obtain a carbon nanotube conductive slurry, wherein the weight percentage of the carbon nanotubes is 3-10%, and the weight percentage of the N-methylpyrrolidone solvent is 90-97%; then 40%±4% of the carbon nanotube conductive slurry is added to the stirring tank, and the stirring tank is stirred at a speed of 200-300 r / min and a speed of 15-2 The mixture is wetted and stirred at a speed of 5 r / min for 30-60 min; thereafter, the remaining carbon nanotube conductive slurry and N-methylpyrrolidone solvent are added to the stirring tank, and stirring is continued for 4-8 h at a revolution speed of 15-25 r / min; subsequently, an appropriate amount of N-methylpyrrolidone solvent is added to the stirring tank in succession, and the speed of the stirring tank is controlled at 4000-5000 r / min in rotation and 10-25 r / min in revolution, and the positive electrode slurry is obtained after stirring for 8-12 h, and the solid content is controlled at 60%-65%.

10. A method for preparing a positive electrode sheet of a low-temperature power lithium-ion battery, using the positive electrode slurry as claimed in claim 8, characterized in that: The following steps are involved: The positive electrode slurry is evenly coated on both sides of the positive electrode current collector carbon-coated aluminum foil to obtain a wet electrode plate, and the single-side coating surface density is controlled to be 65-110g / m 2 ; The wet plate is transferred to a baking room and dried at a temperature of 100-120°C to obtain a compacted density of 2.8-3.5 g / cm 3 The positive electrode.

Citation Information

Patent Citations

  • Lithium-ion battery for automobile starting-stopping system

    CN106876714A

  • Nickel lithium manganate-based positive electrode material of lithium ion battery and preparation method thereof

    CN105355903A

  • Ultra-high multiplying power lithium ion battery for emergency start

    CN106784997A

  • Quick-charging type lithium-ion battery and preparation method thereof

    CN108428867A

  • Polymer lithium ion battery and manufacturing method thereof

    CN113948757A

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN120089800A

  • Composite positive electrode material and preparation method and application thereof

    CN121123238A